2010
DOI: 10.2478/abm-2010-0031
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine scalp nerve block: hemodynamic response during craniotomy, intraoperative and post-operative analgesia

Abstract: Background: Noxious stimuli during craniotomy may induce hypertension and tachycardia, giving rise to morbidity in patients with intracranial hypertension. Craniotomy is followed by moderate level of postoperative pain. Objective: Evaluate the effectiveness of scalp block on hemodynamic response to noxious stimuli, intraoperative fentanyl requirement and post-operative analgesia. Methods: Sixty patients undergoing elective craniotomy were randomly assigned to receive a scalp block with either 0.5% bupivacaine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 24 publications
2
35
0
7
Order By: Relevance
“…Jin-Young Hwang et al reported that SNB with 0.75% levobupivacaine at the end of surgery effectively improved recovery profiles including relieving postoperative pain, reducing patient control analgesia (PCA) consumption, and decreasing the requirement of anti-hypertension agents 26 . Lawan Tuchinda et al 3 showed that scalp block with 0.25% and 0.5% bupivacaine can blunt blood pressure and heart rate responses to noxious stimulus. Bala et al 27 observed that scalp block with 0.5% www.nature.com/scientificreports www.nature.com/scientificreports/ bupivacaine, added with 1:400,000 adrenaline after skin closure, decreased pain scores up to 6 hours postoperatively compared to normal saline group in patients who were received supratentorial craniotomies.…”
Section: Discussionmentioning
confidence: 99%
“…Jin-Young Hwang et al reported that SNB with 0.75% levobupivacaine at the end of surgery effectively improved recovery profiles including relieving postoperative pain, reducing patient control analgesia (PCA) consumption, and decreasing the requirement of anti-hypertension agents 26 . Lawan Tuchinda et al 3 showed that scalp block with 0.25% and 0.5% bupivacaine can blunt blood pressure and heart rate responses to noxious stimulus. Bala et al 27 observed that scalp block with 0.5% www.nature.com/scientificreports www.nature.com/scientificreports/ bupivacaine, added with 1:400,000 adrenaline after skin closure, decreased pain scores up to 6 hours postoperatively compared to normal saline group in patients who were received supratentorial craniotomies.…”
Section: Discussionmentioning
confidence: 99%
“…Meskipun saat ini telah dilakukan berbagai teknik anestesi untuk operasi bedah otak, namun angka kejadian ketidakstabilan hemodinamik pada awal prosedur pembedahan bedah otak saat dilakukan pemasangan pin kepala, insisi kulit kepala, pembukaan periosteum, dan insisi duramater menunjukkan angka kejadian yang cukup tinggi. [1][2] Pin kepala merupakan salah satu alat yang digunakan untuk memfiksasi kepala saat kraniotomi. Pemasangan pin kepala pada scalp akan memicu respons stres yang berpotensi menyebabkan gangguan hemodinamik.…”
Section: Pendahuluanunclassified
“…Scalp block menurunkan kebutuhan opioid dan menurunkan kejadian hipertensi, takikardia, dan stres neuroendokrin. [1][2]9 Penelitian ini bertujuan untuk membandingkan hemodinamik dan kadar glukosa darah sewaktu (GDS) antara fentanil 2 μg/kgBB/jam dan scalp block saat pemasangan pin kepala pada kraniotomi pengangkatan tumor elektif dengan anestesi umum.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations